Biologic therapy in rheumatic diseases - Catay, Erika Roxana; Soriano, Enrique (Revista del Hospital Italiano de Buenos Aires, 2014)
In the last 10 years, the treatment of rheumatic diseases suffereddrastic changes. The development of monoclonal antibodies and fusion recombinant proteinstargeting specific molecules involved in the pathogenesis of inflammatorydiseases have made real changes on the current treatment of these illness. These group of drugs, called biologicagents, proved to produce improvement in the inflammatory process, reduction of disease progression and efficacy in different autoimmune entities. Nevertheless, the appearance of adverse events, mainly infections, led to the development of guidelines for their use.Guidelines are important because the high acquisition costs of biologic treatments makes the generalized use of these drugs untenable for any health system. Biological therapies in rheumatology are nowadays a strong therapeutic option for a group of patients with chronicdiseases, for whom the possibility of getting betterwere unexpected